2021
DOI: 10.1002/jev2.12082
|View full text |Cite
|
Sign up to set email alerts
|

CD9 inhibition reveals a functional connection of extracellular vesicle secretion with mitophagy in melanoma cells

Abstract: Tetraspanins are often used as Extracellular Vesicle (EV) detection markers because of their abundance on these secreted vesicles. However, data on their function on EV biogenesis are controversial and compensatory mechanisms often occur upon gene deletion. To overcome this handicap, we have compared the effects of tetraspanin CD9 gene deletion with those elicited by cytopermeable peptides with blocking properties against tetraspanin CD9. Both CD9 peptide or gene deletion reduced the number of early endosomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 82 publications
1
23
0
Order By: Relevance
“…CD9, a member of the tetraspanin superfamily, has a variety of biological activities and is considered to be functionally crucial [ 19 ]. CD9 is known to accumulate in EVs [ 22 , 23 ]. In this study, we focused on CD9 and investigated the components enriched by magnetic beads with an immobilized CD9 antibody.…”
Section: Discussionmentioning
confidence: 99%
“…CD9, a member of the tetraspanin superfamily, has a variety of biological activities and is considered to be functionally crucial [ 19 ]. CD9 is known to accumulate in EVs [ 22 , 23 ]. In this study, we focused on CD9 and investigated the components enriched by magnetic beads with an immobilized CD9 antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Close relations to CD9 are the tetraspanins CD81 and CD63, which have been shown previously to substitute for CD9 in some circumstances. Overexpression of CD81 partially rescued the infertility phenotype seen in CD9 KO mice [ 39 ] and it was recently demonstrated that CD9 deletion in human melanoma cells was quickly compensated by CD63 expression upregulation [ 40 ]. It would be interesting to perform RNA-seq or SWATH-MS on the cd9 dKOs to identify upregulated RNA and proteins respectively [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Close relations to CD9 are the tetraspanins CD81 and CD63, which have been shown previously to substitute for CD9 in some circumstances. Overexpression of CD81 partially rescued the infertility phenotype seen in CD9 KO mice (Kaji et al 2002) and it was recently demonstrated that CD9 deletion in human melanoma cells was quickly compensated by CD63 expression upregulation (Suárez et al, 2021). It would be interesting to perform RNA-seq or SWATH-MS on the cd9 dKOs to identify upregulated RNA and proteins respectively (Lin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%